Pituitary Macroadenoma and Severe Hypothyroidism: The Link between Brain Imaging and Thyroid Function. (16th August 2021) - Ciancia, Silvia; Cesari, Silvia; Predieri, Barbara; Bernasconi, Sergio; Iughetti, Lorenzo
Abstract : In case of primary hypothyroidism, reactive pituitary hyperplasia can manifest as pituitary (pseudo) macroadenoma. We report the case of a 12-year-old boy who was evaluated for impaired growth velocity and increased body weight. Because of low insulin-like growth factor 1 levels and poor response to the growth hormone stimulation test, brain magnetic resonance imaging was performed and a pituitary macroadenoma was found. Treatment with levothyroxine was started, and thyroid function was evaluated approximately every 40 days to titrate the dosage. After few months of therapy, the size of the macroadenoma decreased and growth hormone secretion normalized. The pituitary returned to normal size in approximately 5 years. The boy went through puberty spontaneously and reached a normal adult height. In a patient affected by primary hypothyroidism, reactive pituitary hyperplasia can cause growth hormone deficiency; however, growth hormone secretion usually normalizes after starting levothyroxine treatment. Pituitary macroadenoma can be difficult to distinguish from severe pituitary hyperplasia; however, pituitary macroadenomas are rare in childhood, and our clinical case underlines how the hormonal evaluation is essential to achieve a correct diagnosis and prevent unnecessary surgery in a context of pituitary mass.